Psychometric Evaluation of the Approach and Avoidance of Alcohol Questionnaire in a Community Sample - Noyes, Emily T. (J Psychopathol Behav Assess, 2019)
Contrary to most theories of alcohol craving, which only consider desires to use, the Ambivalence Model of Craving (AMC) conceptualizes craving bi-dimensionally as the concurrent desires to consume (approach) and desires not to consume (avoid) alcohol. Consistent with the AMC, the Approach and Avoidance of Alcohol Questionnaire (AAAQ) is a 14-item self-reported measure designed to assess alcohol approach and avoidance inclinations. Scores on the AAAQ have been shown to have high reliability and validity in clinical and college student populations, with a two-factor solution emerging in clinical samples of patients with Alcohol Use Disorders (AUDs) and a three-factor solution in samples of college students. However, despite a number of studies examining the use of the AAAQ in clinical and college student samples, to the best of our knowledge there have not been any psychometric evaluations of the AAAQ in community samples. The current study examined the psychometric properties of the AAAQ by examining the factor structure in a community sample (N = 537). Consistent with the results of previous studies utilizing non-clinical samples, a three-factor solution fit the data best and was invariant across gender. Additionally, all three factors were significantly associated with variables of drinking behavior. These results suggest that the AAAQ provides valid and reliable scores that measure approach and avoidance inclinations in community populations.